Causes of repair failure for degenerative mitral valve disease and reoperation outcomes. (3rd January 2018) - Nishida, Hidefumi; Fukui, Toshihiro; Kasegawa, Hitoshi; Kin, Hajime; Yamazaki, Masataka; Takanashi, Shuichiro
Abstract: OBJECTIVES: This study aimed to evaluate the causes of initial mitral valve (MV) repair failure, the details of reoperation and the long-term outcomes of mitral valve re-repair (Re-MVP). METHODS: We retrospectively reviewed 86 patients who underwent reoperation after MV repair for MR due to degenerative disease from October 1991 to December 2015. First, we analysed the initial MV repair data, causes of MV repair failure, reoperation data and long-term outcomes including survival. Second, the patients were classified into 2 groups based on valve related failure or procedure related failure, and the differences between the groups were analysed. RESULTS: Leaflet prolapse at the initial operation affected the bilateral leaflets in 37 (43%) patients, the anterior leaflet in 30 (35%) patients and the posterior leaftlet in 19 (22%) patients. Median duration from first operation to reoperation was 47.5 (interquartile range 4.8–85.8) months. Reoperation indication included recurrent mitral regurgitation alone in 59 patients, haemolysis combined with recurrent mitral regurgitation in 15 patients, infectious endocarditis combined with recurrent mitral regurgitation in 8 patients, mitral stenosis in 2 patients and left ventricular pseudoaneurysm in 2 patients. The cause of MV repair failure was valve-related in 61 (71%) patients, procedure-related in 20 (23%) patients and both in 5 (6%) patients. Re-MVP was successful in 23 (27%) patients. Re-MVP was more common in patients with procedure-related failure, which occurred earlier than valve-related failure. Freedom from all-cause death was significantly better after Re-MVP. The 5-year freedom from reoperation after Re-MVP was 95.7%. CONCLUSIONS: Re-MVP was more common in patients with procedure-related failure, which occurred earlier than valve-related failure. Durability of re-repaired MVs and survival of re-repaired patients were acceptable.